Golden grey mullet and sea bass oxidative DNA damage and clastogenic/aneugenic responses in a contaminated coastal lagoon - Oliveira, M. (2010)
Several xenobiotics or their metabolites have redox-cycling properties and potential to induce oxidative stress and DNA damage. The current work aimed to study, under environmental conditions, oxidative DNA damage (8-hydroxy-2′-deoxyguanosine (8-OHdG)) and its association with chromosomal damage measured as erythrocytic nuclear abnormalities (ENAs), in Liza aurata and Dicentrarchus labrax, caught at a costal lagoon (Ria de Aveiro, Portugal) having sites with different contamination profiles. The quantified parameters were also used to assess the lagoon’s environmental status. Five critical sites were assessed comparing to a reference site. L. aurata displayed higher 8-OHdG levels and ENAs frequency, respectively, at Laranjo and Vagos. D. labrax 8-OHdG levels were higher at the sites where quantification was possible whereas no differences were found in terms of ENAs. No correlation was found in both species between 8-OHdG and ENAs. Despite no direct linkage between the two biomarkers was found, this study demonstrates species and site dependent genotoxic responses.